Libor Rate Scandals and Casino Capitalism: criminal Fraud in Worldwide Financial Markets - Calathes, William (Law, crime & history, 2023)
This paper examines Libor rate scandals as examples of global financial deviance resulting in worldwide economic victimization. The mechanics of the scandals are detailed, with theories presented highlighting the political-economic influences underlying their perpetration. An examination of a number of criminal and civil Libor cases are also provided showing that Libor bid-rigging was more than simple organizational or occupational deviance, but rather were deviant practices provided by structural opportunities. In reviewing the inadequate responses to these practices, the paper concludes by introducing arguments for a measure of public control and more aggressive state-regulation of global finance.